Bunny call - Cawthon, Scott, 1971- (Cawthon, Scott, 1971- Five nights at Freddy's. Fazbear frights, 2020)
When left in darkness, rage festers. Years of frustration with his family culminate in a loathsome vacation for Bob, who plots a sinister prank to frighten his wife and kids. Matt redirects the residual anger over his many failed relationships into a video game, and ends up birthing the horrible consequences. In room 1280 of Heracles Hospital, something evil is keeping a man alive, a man with gruesome burns all over his body and an iron will to live.